Design and feasibility study of a standalone photovoltaic system for electrifying a healthcare centre in a rural area of Malaysia: a case study - Wan Robiah Wan Ismail; Norlie Yuzanna Ibrahim; Shafura Sharif; Normazlina Mat Isac; Anies Faziehan Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malaysia is strategically located at the sunbelt viability, where it receives a large amount of sunshine every day. This makes the solar photovoltaic technology popularly utilized particularly in rural areas that are isolated from the main grid. These areas have the potential to use photovoltaic technology to meet load requirements. Compared to grid connected photovoltaic systems, standalone photovoltaic systems offer several benefits to system owners including low maintenance, low upkeep cost, no waste or by-products, and easy expansion through the use of multiple solar panels and batteries. This article presents a design phase of the Standalone Photovoltaic System (SAPVS) to electrify the healthcare centre in Kampung Tewowoh, Kluang, Johor. The design steps for SAPVS are discussed to obtain the required parameter for each component in the SAPVS. The results indicate that 16 panels, 1219.52Ah/day, 1437.5A and 350 (A) are needed for the PV panels, battery capacity, inverter, and charge controller, respectively. It is proven that SAPVs are technically viable and feasible for electrifying the healthcare centre in the specified area